HEMATOLOGIC PARAMETERS AS PREDICTOR OF COVID-19 SEVERITY - Angky Saputra; Vincentius Diamantino Supit; Margaret Gabriele Helena; Margareth Ayuni Trinatha Alfares; Vicky Sanrio Angky (FAKULTAS KEDOKTERAN UNIVERSITAS KATOLIK WIDYA MANDALA SURABAYA, 2021)
Introduction: To this day, COVID-19 still cause high mortality and morbidity in most cases. The severity of COVID-19 can be detected by simple tests such as complete blood counts which available in most health facilities. Through early detection of the estimated severity of COVID-19, we may determine which patients need hospitalization or patients sufficient with self-isolation. Methods: We conduct an analytical, cross-sectional, retrospective study that analyzed the hematological parameters of 97 patients with positive rRT-PCR swabs in the period of March to August 2020. Hematologic parameters of COVID 19 patients with mild and moderate-severe symptoms were compared. The receiver operating characteristic (ROC) curve, area under the curve (AUC), and Youden's index were created to determine the optimal cut-off value in predicting the degree of severity of COVID-19 patients. Results: Statistically significant differences (p